An Analysis of the Socio-Economic Integration of Nigerian Migrants in Ghana - Quaye, D.H. (University Of Ghana, 2019)
Migration to Ghana from post-independence era to recent times has been mainly dominated by Nigerians. Factors such as economic opportunities, peace and stability in Ghana as well as the free movement ECOWAS Protocol are among the key determinants of Nigerian migration to Ghana. Since this era, Ghana has experienced migration and integration of Nigerians in the country. While this protocol helps these migrants to move to Ghana, it does not explicitly tackle the issues they face in their effort at integrating in Ghana. The study adopts integration as a conceptual framework in explaining the social and economic factors that facilitate integration of Nigerian migrants in Ghana. The study indicates that social networks, access to education, housing and labour market are among the socio-economic factors that facilitate integration of Nigerian migrants in Ghana. The study employs a qualitative research method and relies on both primary and secondary data to draw conclusions. Nigerians face some challenges in the social and economic aspects of their integration process in Ghana. The Government of Ghana on her part has enacted policies that facilitate the integration of these migrants, however, these policies have not yielded all the expected outcomes. To achieve self-sufficiency for its members and promote their socio-economic integration in Ghana, recommendations are therefore made for ECOWAS to have a partnership agreement with Ghana to subsidize school fees for international students from countries in the ECOWAS community. Also, it is important for the GoG to broaden the constitution to allow foreign nationals the right to acquire and develop lands in Ghana to address the challenges Nigerians have with housing which impede their socio-economic integration. Additionally, the trading and investment sector of Ghana must be reconstructed to position the country in a way that will benefit from Nigerians who are engaged in businesses in Ghana.
MA. International Affairs
Keywords: Migration; Nigerian Migrants; Ghana